Interleukin-22 Promotes Intestinal Stem Cell-Mediated Epithelial Regeneration - Lindemans, Caroline A. (Nature, 2015)
Epithelial regeneration is critical for barrier maintenance and organ function after intestinal injury. The intestinal stem cell (ISC) niche provides Wnt, Notch, and epidermal growth factor (EGF) signals supporting Lgr5(+) crypt base columnar ISCs for normal epithelial maintenance(1,2). However, little is known about the regulation of the ISC compartment after tissue damage. Utilizing ex vivo organoid cultures, we provide evidence that innate lymphoid cells (ILCs), potent producers of Interleukin-22 (IL-22) after intestinal injury(3,4), increased the growth of murine small intestine (SI) organoids in an IL-22-dependent fashion. Recombinant IL-22 directly targeted ISCs, augmenting the growth of both murine and human intestinal organoids, increasing proliferation, and promoting ISC expansion. IL-22 induced Stat3 phosphorylation in Lgr5(+) ISCs, and Stat3 was critical for both organoid formation and IL-22-mediated regeneration. Treatment with IL-22 in vivo after murine allogeneic bone marrow transplantation (BMT) enhanced recovery of ISCs, increased epithelial regeneration, and reduced intestinal pathology and mortality from graft vs. host disease (GVHD). Atoh1-deficient organoid culture demonstrated that IL-22 induced epithelial regeneration independent of the Paneth cell niche. Our findings reveal a fundamental mechanism by which the immune system is able to support intestinal epithelium, activating ISCs to promote regeneration.